Low lean mass and all-cause mortality risk in the middle-aged and older population: a dose-response meta-analysis of prospective cohort studies - Li, Juan; Liu, Xiaoling; Yang, Qing; Huang, Wenying; Nie, Zhibin; Wang, Yahai (Frontiers in Medicine, 2025)
ObjectiveThe accelerated aging process has raised substantial public health concerns regarding the health of the middle-aged and older population. The aim of our study was to investigate the association between low lean mass and the risk of all-cause mortality in older people, with the goal of promoting a long lifespan and reducing public health burdens.MethodsThree databases (PubMed, Web of Science, and Scopus) were searched for articles before May 22, 2025. The quality of the included articles was assessed using the Newcastle-Ottawa Scale (NOS). A meta-analysis was conducted using a random effects model. Subgroup analysis and meta-regression analysis were performed based on research characteristics. A dose-response analysis was performed to assess the specific association between lean mass and the risk of all-cause mortality. Sensitivity analysis was conducted using a leave-one-out meta-analysis. Publication bias analysis was conducted using Begg’s and Egger’s tests, as well as a funnel plot.ResultsIn total, 11 studies involving 130,079 participants were included in the meta-analysis of the association between low lean mass and the risk of all-cause mortality in the middle-aged and older population, all of which the included studies were of high quality. The average overall study quality score was 8 points. The random effects model analysis results showed that the pooled RR of all-cause mortality risk in the middle-aged and older population was 1.30 (95% CI, 1.16–1.47, P < 0.001) across the lowest to normal lean mass category. There was an inverse non-linear dose-response relationship between lean mass and the risk of all-cause mortality (P < 0.001).ConclusionLow lean mass was significantly associated with 30% higher risk of all-cause mortality in the middle-aged and older population. These findings highlighted low lean mass as an important risk factor for mortality in middle-aged and older population, warranting its integration into clinical assessments. Future research should establish causality through longitudinal studies and randomized trials, while refining diagnostic cutoffs for diverse populations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/#myprospero, Identifier CRD42023445297.